Remission of Suicidal Ideation in Emotionally Unstable Personality Disorder with Flupenthixol - Chivers, Daniel J.; Shaffiullah, Mohammed (Case Reports in Psychiatry, 2022)
There are currently no licensed pharmacological treatments for Emotionally Unstable Personality Disorder. This case report describes a 50-year-old male who two years previously had been brought to the attention of psychiatric services following an overdose with intention to end his life. He was subsequently diagnosed with Emotionally Unstable Personality Disorder (EUPD) and, following further suicide attempts and trials of mainstream pharmacological treatments, responded to flupenthixol IM 20 mg fortnightly, experiencing complete remission from his suicidal ideation. Clinicians should be aware of EUPD presenting in later life and should consider the role of typical antipsychotics, including flupenthixol, in the treatment of suicidal ideation in patients with EUPD. Age-specific guidance on EUPD management would be of use to clinicians, especially in the management of older patients, as current guidance is based on findings within a narrow age group.